EP4 Antagonism by E7046 diminishes Myeloid immunosuppression and synergizes with Treg-reducing IL-2-Diphtheria toxin fusion protein in restoring anti-tumor immunity. (3rd August 2017) - Albu, Diana I.; Wang, Zichun; Huang, Kuan-Chun; Wu, Jiayi; Twine, Natalie; Leacu, Sarah; Ingersoll, Christy; Parent, Lana; Lee, Winnie; Liu, Diana; Wright-Michaud, Renee; Kumar, Namita; et al.
ABSTRACT: Reprogramming of immunosuppressive tumor microenvironment (TME) by targeting alternatively activated tumor associated macrophages (M2TAM), myeloid-derived suppressor cells (MDSC), and regulatory T cells (Tregs), represents a promising strategy for developing novel cancer immunotherapy. Prostaglandin E2 (PGE2 ), an arachidonic acid pathway metabolite and mediator of chronic inflammation, has emerged as a powerful immunosuppressor in the TME through engagement with one or more of its 4 receptors (EP1-EP4). We have developed E7046, an orally bioavailable EP4-specific antagonist and show here that E7046 has specific and potent inhibitory activity on PGE2 -mediated pro-tumor myeloid cell differentiation and activation. E7046 treatment reduced the growth or even rejected established tumors in vivo in a manner dependent on both myeloid and CD8 + T cells. Furthermore, co-administration of E7046 and E7777, an IL-2-diphtheria toxin fusion protein that preferentially kills Tregs, synergistically disrupted the myeloid and Treg immunosuppressive networks, resulting in effective and durable anti-tumor immune responses in mouse tumor models. In the TME, E7046 and E7777 markedly increased ratios of CD8 + granzymeB + cytotoxic T cells (CTLs)/live Tregs and of M1-like/M2TAM, and converted a chronic inflammation phenotype into acute inflammation, shown by substantial induction of STAT1/IRF-1 and IFNγ-controlled genes. Notably, E7046 also showed synergistic anti-tumor activity when combined with anti-CTLA-4 antibodies, which have been reported to diminish intratumoral Tregs. Our studies thus reveal a specific myeloid cell differentiation-modifying activity by EP4 blockade and a novel combination of E7046 and E7777 as a means to synergistically mitigate both myeloid and Treg-derived immunosuppression for cancer treatment in preclinical models.